Cancer Stemness Associated With Prognosis and the Efficacy of Immunotherapy in Adrenocortical Carcinoma - Shi, Xiaoxi; Liu, Yuanlin; Cheng, Shuai; Hu, Haidi; Zhang, Jian; Wei, Minjie; Zhao, Lin; Xin, Shijie (Frontiers in Oncology, 2021)
Cancer stem cells (CSCs) have been proved to influence drug resistance, recurrence and metastasis in tumors. Our study aimed to identify stemness-related prognostic biomarkers for new therapeutic strategies in adrenocortical carcinoma. RNA-seq data and clinical characteristics were downloaded from The Cancer Genome Atlas (TCGA). Calculating the stemness indexes, mDNAsi and mRNAsi, to classify all samples into low-score and high-score groups. Two algorithms, based on R language, ESTIMATE and single-sample Gene Set Enrichment Analysis (ssGSEA) were used to assess the immune cell infiltration states of adrenocortical carcinoma patients. Weighted Gene Co-expression Network Analysis (WGCNA) was used to find genes that were related to the stemness of cancer. By bioinformatics methods, the correlations between biomarkers that capable of predicting immune checkpoint inhibitors (ICIs) responses and stemness of cancer were explored. High-mRNAsi predicted shorter Overall Survival (OS) and higher metastatic trend in ACC patients. Compared with low-mRNAsi group, high-mRNAsi group had a lower ImmuneScore and StromalScroe. 22 stemness-related prognostic genes were obtained by WGCNA, which focused on the function of cell cycle and cell mitosis. Immune cell infiltration, especially CD8+T cell, increased in low-mRNAsi group compared with high-mRNAsi group. Lower expression of PD-L1, CTLA-4 and TIGHT was evaluated in high-mRNAsi group. ACC patients with high-mRNAsi have poor prognosis and less immune cell infiltration. Combined with the finding of lower expression of CTLA-4, TIGHT and PD-L1 in high-mRNAsi group, we came to the conclusion that stemness index is a potential biomarker to predict the effectiveness of ICIs